Criminalizing human trafficking has not made a difference: a law enforcement failure - Dandurand, Yvon (Bridging the gaps in our efforts to combat human trafficking, 2026)
Law enforcement efforts of the past 20 years have failed to curb human trafficking and migrant smuggling. There are many reasons for the failure of the present anti-human trafficking regime. If law enforcement and prosecution efforts against human trafficking have proved inept, it may be due less to weak international or national legal frameworks than to a general law enforcement negligence to address the problem effectively. Added to that is the progressive disinvestment from international law enforcement cooperation, which has led law enforcement agencies to ignore the transnational nature of human trafficking and redefine it as a primarily domestic problem. Enforcement agencies must move beyond reactive responses and adopt strategic and proactive approaches to investigating and prosecuting organized crime and human trafficking. Ideas are offered on how to reverse the blatant lack of law enforcement attention to human trafficking, especially labor trafficking.